Sublethal effects of imidacloprid on the fitness of two species of wheat aphids, Schizaphis graminum (R.) and Rhopalosiphum padi (L.). - Xiang Ji; Yu-Tai Jiang; Tian-Xin Guo; Pei Zhang; Xin-An Li; Fan-Bin Kong; Bai-Zhong Zhang (PLoS ONE, 2023)
Imidacloprid is a neonicotinoid insecticide that efficiently controls piercing-sucking mouthparts pests. However, the impact of low lethal concentration of imidacloprid on key demographic parameters of wheat aphids, Schizaphis graminum (R.) and Rhopalosiphum padi (L.) has been scarcely studied. In this study, we used the age stage, two-sex life table approach to investigate the sublethal effects of imidacloprid on the biological traits of S. graminum and R. padi. Bioassays showed that imidacloprid possesses high toxicity to adult S. graminum and R. padi, with LC50 of 3.59 and 13.78 mg L-1 following 24 h exposure. A low lethal concentration of imidacloprid (LC25) significantly decreased adult longevity and total longevity of progeny generation aphids (F1) of S. graminum. Nevertheless, imidacloprid (LC25) had no significant effects on the fecundity and longevity of directly exposed parental parental S. graminum and R. padi (F0). Our results showed that the low lethal concentration of imidacloprid affected the demographic parameters that ultimately impact on the population of S. graminum. This study provides detailed information about the overall effects of imidacloprid on S. graminum and R. padi that might help to manage these two key pests.